Medical Applications Based on Supramolecular Self-Assembled Materials From Tannic Acid - Lu, Ruofei; Zhang, Xiaoqiang; Cheng, Xinxiu; Zhang, Yagang; Zan, Xingjie; Zhang, Letao (Frontiers in Chemistry, 2020)
Polyphenol, characterized by various phenolic rings in the chemical structure and an abundance in nature, can be extracted from vegetables, grains, chocolates, fruits, tea, legumes, and seeds, among other sources. Tannic acid (TA), a classical polyphenol with a specific chemical structure, has been widely used in biomedicine because of its outstanding biocompatibility and antibacterial and antioxidant properties. TA has tunable interactions with various materials that are widely distributed in the body, such as proteins, polysaccharides, and glycoproteins, through multimodes including hydrogen bonding, hydrophobic interactions, and charge interactions, assisting TA as important building blocks in the supramolecular self-assembled materials. This review summarizes the recent immense progress in supramolecular self-assembled materials using TA as building blocks to generate different materials such as hydrogels, nanoparticles/microparticles, hollow capsules, and coating films, with enormous potential medical applications including drug delivery, tumor diagnosis and treatment, bone tissue engineering, biofunctional membrane material, and the treatment of certain diseases. Furthermore, we discuss the challenges and developmental prospects of supramolecular self-assembly nanomaterials based on TA.